2020
DOI: 10.1016/j.jsxm.2020.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Based Devices for Female Genitourinary Indications: Position Statements From the European Society for Sexual Medicine (ESSM)

Abstract: Background Laser-based technologies have been commercially marketed as “wonder treatments” without a sufficient and adequate body of evidence. In addition, on July 30, 2018, the U.S. Food and Drug Administration issued a warning regarding the safety of the use of laser-based devices for the following indications: vaginal “rejuvenation” or cosmetic vaginal procedures, vaginal conditions and symptoms related to menopause, urinary incontinence, and sexual function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…[128][129][130][131][132] The value of local testosterone application and of invasive measures like vaginal laser or hyaluronic acid injections is still unclear. [133][134][135] In summary, gynaecological and sexual symptoms are important challenges for most ABC patients. In particular, even in an anonymous setting, patients are often too shy to report their problems regarding impaired sexual life.…”
Section: Iv/b 86%mentioning
confidence: 99%
“…[128][129][130][131][132] The value of local testosterone application and of invasive measures like vaginal laser or hyaluronic acid injections is still unclear. [133][134][135] In summary, gynaecological and sexual symptoms are important challenges for most ABC patients. In particular, even in an anonymous setting, patients are often too shy to report their problems regarding impaired sexual life.…”
Section: Iv/b 86%mentioning
confidence: 99%
“…Professional bodies such as the North American Menopause Society (NAMS) and the International Society for the study of Women’s Sexual Health (ISSWSH) in a consensus recommendation have stated that when treating GSM in women that are high risk for breast cancer, the microablative fractional CO2 laser, or other non-ablative energy-based treatments, can offer a potential advantage over pharmacologic therapies [ 6 ]. Other professional organizations such as the European Society for Sexual Medicine (ESSM) and the International Urogynecological Association (IUGA) issued committee opinions stating that therapeutic advantages of nonsurgical laser-based treatments can only be recommended after robust clinical trials that will demonstrate their short-/long-term benefits and complication profile [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism of how this type of treatment works is still unknown [27], several studies showed the benefit of laser treatment in menopausal genitourinary syndromes and breast cancer survivors [20]. Unfortunately, these studies included only a small number of patients, did not report on side effects and long-term results and were performed with different types of lasers (CO 2 , erbium) [24]. However, a systematic review described a rapid and statistically significant benefit on vaginal tissues with improved self-reported outcomes and clinical parameters [20].…”
Section: Discussionmentioning
confidence: 99%
“…Intravaginal laser therapy is a new non-pharmacological treatment successfully proposed especially for the management of symptoms produced by menopausal genital atrophy. Due to the satisfactory efficacy of this treatment, the term "vaginal rejuvenation" has been proposed by some authors [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%